Proses Berpikir Kritis Matematis Siswa Dalam Menyelesaikan Soal Pisa Konten Change And Relationship Ditinjau Dari Self-Regulated Learning - Ervin Oktavianingtyas; Fina Feby Angelia; Dhanar Dwi Hary Jatmiko; Dinawati Trapsilasiwi; Inge Williandani Setya Putri (Universitas Swadaya Gunung Djati, 2025)
Critical thinking is very necessary to face the development of the era that continues to develop. The international instrument that is often used to measure mathematical critical thinking skills is the Programme for International Student Assessment (PISA). This qualitative research with a descriptive approach aims to describe the process of students' mathematical critical thinking in solving PISA questions on the content of change and relationship in terms of self-regulated learning. The subjects of this study were one subject with a high self-regulated learning category and one subject with a moderate self-regulated learning category in grade VIII. The selection of subjects was based on the results of the self-regulated learning questionnaire criteria and the results of critical thinking tests. The results of the analysis obtained showed that students with high self-regulated learning had a superior mathematical critical thinking process compared to students with moderate self-regulated learning. Subjects with high self-regulated learning not only understood the questions well, but were also able to analyze them in depth, evaluate the results of their work, and draw logical and relevant conclusions. In contrast, subjects with moderate self-regulated learning were still able to solve the questions, but with simpler strategies and less in-depth thinking. They tended to follow standard procedures without further exploration of the concepts underlying problem solving.